RAR-related orphan receptor alpha and the staggerer mice: a fine molecular story - Rani, Aradhana (Frontiers in Endocrinology, 2024)
The retinoic acid-related orphan receptor alpha (RORα) protein first came into the limelight due to a set of staggerer mice, discovered at the Jackson Laboratories in the United States of America by Sidman, Lane, and Dickie (1962) and genetically deciphered by Hamilton et al. in 1996. These staggerer mice exhibited cerebellar defects, an ataxic gait, a stagger along with several other developmental abnormalities, compensatory mechanisms, and, most importantly, a deletion of 160 kilobases (kb), encompassing the RORα ligand binding domain (LBD). The discovery of the staggerer mice and the subsequent discovery of a loss of the LBD within the RORα gene of these mice at the genetic level clearly indicated that RORα’s LBD played a crucial role in patterning during embryogenesis. Moreover, a chance study by Roffler-Tarlov and Sidman (1978) noted reduced concentrations of glutamic acid levels in the staggerer mice, indicating a possible role for the essence of a nutritionally balanced diet. The sequential organisation of the building blocks of intact genes, requires the nucleotide bases of deoxyribonucleic acid (DNA): purines and pyrimidines, both of which are synthesized, upon a constant supply of glutamine, an amino acid fortified in a balanced diet and a byproduct of the carbohydrate and lipid metabolic pathways. A nutritionally balanced diet, along with a metabolic “enzymatic machinery” devoid of mutations/aberrations, was essential in the uninterrupted transcription of RORα during embryogenesis. In addition to the above, following translation, a ligand-responsive RORα acts as a “molecular circadian regulator” during embryogenesis and not only is expressed selectively and differentially, but also promotes differential activity depending on the anatomical and pathological site of its expression. RORα is highly expressed in the central nervous system (CNS) and the endocrine organs. Additionally, RORα and the clock genes are core components of the circadian rhythmicity, with the expression of RORα fluctuating in a night–day–night sigmoidal pattern and undoubtedly serves as an endocrine-like, albeit “molecular–circadian regulator”. Melatonin, a circadian hormone, along with tri-iodothyronine and some steroid hormones are known to regulate RORα-mediated molecular activity, with each of these hormones themselves being regulated rhythmically by the hypothalamic–pituitary axis (HPA). The HPA regulates the circadian rhythm and cyclical release of hormones, in a self-regulatory feedback loop. Irregular sleep–wake patterns affect circadian rhythmicity and the ability of the immune system to withstand infections. The staggerer mice with their thinner bones, an altered skeletal musculature, an aberrant metabolic profile, the ataxic gait and an underdeveloped cerebellar cortex; exhibited compensatory mechanisms, that not only allowed the survival of the staggerer mice, but also enhanced protection from microbial invasions and resistance to high-fat-diet induced obesity. This review has been compiled in its present form, more than 14 years later after a chromatin immunoprecipitation (ChIP) cloning and sequencing methodology helped me identify signal transducer and activator of transcription 5 (STAT5) target sequences, one of which was mapped to the first intron of the RORα gene. The 599-base-long sequence containing one consensus TTCNNNGAA (TTCN3GAA) gamma-activated sequence (GAS) and five other non-consensus TTN5AA sequences had been identified from the clones isolated from the STAT5 target sites (fragments) in human phytohemagglutinin-activated CD8+ T lymphocytes, during my doctoral studies between 2006 and 2009. Most importantly, preliminary studies noted a unique RORα expression profile, during a time-course study on the ribonucleic acid (RNA), extracted from human phytohemagglutinin (PHA) activated CD8+ T lymphocytes stimulated with interleukin-2 (IL-2). This review mainly focuses on the “staggerer mice” with one of its first roles materialising during embryogenesis, a molecular-endocrine mediated circadian-like regulatory process.